Growth Kinetics of Ethidium Bromide Mutagenized Lipomyces starkeyi Strains - Micky, Vincent; Lesley, Maurice Bilung; Latifah, Suali; AfIzul Safwan, Azahari; Patricia Rowena, Mark Baran Saging; Elexson, Nillian (Penerbit Akademia Baru, 2018)
Yeast and growth and biomass production are greatly influenced by the length of the incubation period during cultivation. Therefore, this study was conducted to investigate the growth kinetics of five Lipomyces starkeyi strains as determined by biomass production. The five L. starkeyi strains, namely L. starkeyi ATCC 12659, L. starkeyi MV-1, L. starkeyi MV-4, L. starkeyi MV-5 and L. starkeyi MV-8, were inoculated in sterilized Yeast Malt broth, and, incubated for 192 hr at ambient temperature. Biomass yields were assessed and calculated gravimetrically every 24 hr. Results indicated that the optimal biomass production of L. starkeyi ATCC 12659, L. starkeyi MV-1, L. starkeyi MV-4, L. starkeyi MV-5 and L. starkeyi MV-8 were at 120, 168, 144, 168 and 120 hr, with the concentrations of 6.64, 6.43, 9.78, 11.23 and 8.56 g/L, respectively. These results indicate that each L. starkeyi strain requires specific incubation period for the optimum production of fungal biomass. Therefore, by cultivating each L. starkeyi strain at the predetermined incubation period, biomass yields could significantly be improved for further downstream applications such as single cell protein and lipid production.